2018
DOI: 10.1029/2018jd028531
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Redistribution Method for Regional Simulations of Radioactive Material Transport During the Fukushima Daiichi Nuclear Power Plant Accident

Abstract: To reproduce more accurate deposition maps of radioactive materials released in the Fukushima Daiichi Nuclear Power Plant accident in March 2011, our study focuses on the uncertainty of atmospheric transport simulations caused by precipitation. In our new method, simulated wet deposition distribution of 137Cs is modified by high‐resolution radar rain gauge data of observed precipitation. Sensitivity experiments are conducted to examine the impact of using both different reanalyzed meteorological data sets as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It should also be noted that both the GCM-type method with proper tuning parameters and the conventional method These findings suggest that the differences in cloud microphysics treatments among the various models, e.g., MIPs, do not primarily cause the differences in the simulated Cs-137 distribution. Saya et al (2018) suggested that a better simulation of precipitation provides a closer deposition amount of simulated Cs-137 to the observation. Sekiyama et al (2021) implies that a high accuracy of the simulated Cs-137 needs much higher accuracy of the meteorological fields.…”
Section: Discussionmentioning
confidence: 97%
“…It should also be noted that both the GCM-type method with proper tuning parameters and the conventional method These findings suggest that the differences in cloud microphysics treatments among the various models, e.g., MIPs, do not primarily cause the differences in the simulated Cs-137 distribution. Saya et al (2018) suggested that a better simulation of precipitation provides a closer deposition amount of simulated Cs-137 to the observation. Sekiyama et al (2021) implies that a high accuracy of the simulated Cs-137 needs much higher accuracy of the meteorological fields.…”
Section: Discussionmentioning
confidence: 97%
“…In total, nine models (M1, M2, M4, M5, M6, M11, M12, M13, and M14; these numbers are unified for MICS-Asia phase III) were used in this deposition analysis; these models are summarized in an overview paper (Itahashi et al, 2020, Table 1). In this study, seven models (M1, M2, M4, M5, M6, M11, and M12) that using the same meteorological fields simulated by the Weather Research and Forecasting (WRF) model version 3.4.1 (Skamarock et al, 2008) over the unified modeling domain were selected. The unified modeling domain covered the whole of Asia with a horizontal grid resolution of 45 km and 40 vertical layers from the surface up to 10 hPa.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Here, it is assumed that the errors in the modeled precipitation are linearly associated with the errors in the modeled wet deposition. This approach has been used in previous studies in the US (Appel et al, 2011;Zhang et al, 2018) and east Asia (Itahashi, 2018;Saya et al, 2018). Following our previous work in MICS-Asia III for deposition (Itahashi et al, 2020), wet depositions were adjusted on a monthly timescale and then the annual wet deposition was recalculated using the precipitationadjusted monthly wet deposition.…”
Section: Proposal Of Precipitation-adjusted Approach Over Southeast Asiamentioning
confidence: 99%
“…Here, supposing that the errors in the modeled precipitation are linearly associated to the errors in the modeled wet deposition. This approach has been used in previous studies in the U.S.A. (Appel et al, 2011;Zhang et al, 2018) and East Asia (Itahashi, 2018;Saya et al, 2018). Following our previous work in MICS-Asia III for deposition (Itahashi et al, 2020), wet depositions were adjusted on a monthly time scale and then the annual wet deposition was recalculated from precipitation-adjusted monthly wet deposition.…”
Section: Proposal Of Precipitation-adjusted Approach Over Southeast Asiamentioning
confidence: 99%